Technical challenges in using human induced pluripotent stem cells to model disease - Saha, Krishanu (2009)
Reprogramming of human somatic cells uses readily accessible tissue, such as skin or blood, to generate embryonic-like induced pluripotent stem cells (iPSCs). This procedure has been applied to somatic cells from patients who are classified into a disease group, thus creating ‘disease-specific’ iPSCs. Here we examine the challenges and assumptions in creating a disease model from a single cell of the patient. Both the kinetics of disease onset and progression as well as the spatial localization of disease in the patient’s body are challenges to model construction. New tools in genetic modification, reprogramming, biomaterials, and animal models can be used to address these challenges.